Diagnostic evaluation and management of culture‐negative cardiovascular implantable electronic device infections. Issue 8 (21st June 2018) - Esquer Garrigos, Zerelda; George, Merit P.; Farid, Saira; Abu Saleh, Omar M.; Vijayvargiya, Prakhar; Mahmood, Maryam; Friedman, Paul A.; Steckelberg, James M.; DeSimone, Daniel C.; Wilson, Walter R.; Baddour, Larry M.; Sohail, M. Rizwan
Abstract: Background: Culture‐negative (CN) cardiovascular implantable electronic device (CIED) infections represent a significant management challenge for clinicians with no specific guidelines addressing this subgroup of patients. The aim of the current investigation is to report our institutional experience of CN CIED infections and propose a systematic approach to diagnostic evaluation and management of these complicated cases based on our observations. Methods: We retrospectively screened all CIED infection cases at Mayo Clinic from 2005 through 2017. Using standardized criteria to define significant microbial growth, all patients with positive blood or pocket/device cultures were excluded. Results: A total of 835 cases of CIED infection were screened, and of these, 47 (6%) met CN‐CIED infection criteria. Majority of patients (77%) in this cohort had received antimicrobial therapy prior to device cultures with a median duration of 8 days. The most common presentation was device pocket infection (81%). All patients underwent device removal. Route of antibiotics was switched from oral to parenteral and spectrum of activity expanded from initial therapy in 23% of patients despite negative cultures. Majority of patients (80%) were dismissed on parenteral therapy. Adverse events attributed to intravenous antibiotic therapy were documented in 63% of the cases. No recurrence was reported and 6‐month survival was 94.8%. Conclusions: Pocket and device cultures in suspected CIED infections may be negative due to preextraction oral antibiotics. However, frequently these patients are managed with broad‐spectrum parenteral therapy postextraction.